Evaluation of the Short-Term Music Therapy on Brain Functions of Preterm Infants Using Functional Near-Infrared Spectroscopy - Ren, Haoran; Zou, Liangyan; Wang, Laishuan; Lu, Chunmei; Yuan, Yafei; Dai, Chenyun; Chen, Wei (Frontiers in Neurology, 2021)
Music contains substantial contents that humans can be perceived, and thus has capability to evoke positive emotions. Even though the neonatal intensive care unit (NICU) can provide preterm infants a developmental environment, it still cannot fully simulate the environment in the womb. The reduced maternal care would increase stress levels in premature infants. Fortunately, the music intervention has been proved that it can improve the NICU environment, such as stabilize heart rate and respiratory rate, reduce the incidence of apnea, and improve feeding. However, the effects of music therapy on the brain development of preterm infants need to be further investigated. In this paper, we evaluated the influence of short-term music therapy on the brain functions of preterm infants measured by functional Near-infrared spectroscopy (fNIRS). We began by investigating how premature babies perceive structural information of music by calculating the correlations between music features and fNIRS signals. Then, the influences of short-term music therapy on brain functions were evaluated by comparing the resting-state functional connectivity before and after the short-term music therapy. The results show that the distinct brain regions are responsible for processing corresponding musical features, indicating that preterm infants have capability to process the complex musical content. However, the results of network analysis show that short-term music intervention is insufficient to cause the changes in cerebral functional connectivity. Therefore, long-term music therapy may be required to achieve the deserved effects on brain functional connectivity.